Perceptions of Work–Family–Engineering Relationships Among Employed Female Engineers in Yemen: A Survey Study - Atef M. Ghaleb; Laila Abdulkhaliq; Halah Abd Al-nour; Mokhtar Ali Amrani; Hanaa A. Hebah; Sobhi Mejjaouli (Societies)
Work–family conflict (WFC) is a worldwide and timeless dilemma that negatively and significantly impacts the performance of employees, families, and organizations. It intensifies when the career is engineering, the employee is female, and the job environment requires heavy-duty and field tasks. The present study investigates the WFC in an engineering environment for female engineers and studies many women-related issues in Yemen. Three questionnaires targeted 130 female engineer graduates, 60 senior engineers, and 20 female engineers’ husbands. The results indicated that marriage is strongly and negatively correlated to educational performance, job opportunities, and job continuity. The present study suggests that, in conservative societies, disruptions from family-to-work are more pronounced compared to work-to-family. Several external factors, including low stipends, economic downturns, and political crises, have a negative impact on job opportunities and job spillover. A significant finding revealed that the average wage of female engineers in Yemen is USD 145, which is 3.822 times lower than that of their male counterparts. The survey results indicated that only single female engineers, but not married female engineers, are currently employed in the industrial and construction sector. Most female engineering graduates are working in jobs unrelated to engineering. Employed females face balancing professional responsibilities, household tasks, and social commitments. Society needs to implement policies that alleviate the pressure on women’s work and promote and support dual-earning couples to enhance family income. The present study recommends organizations offer flexible work schedules, allow remote work options, and create a healthy work environment to address the work–family imbalance, particularly in male-dominated environments.